2020
DOI: 10.3390/atmos11070761
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Solar Climate Atlas for Greece under Climate Change Using the Weather Research and Forecasting (WRF) Model

Abstract: In the context of climate change and growing energy demand, solar technologies are considered promising solutions to mitigate Greenhouse Gas (GHG) emissions and support sustainable adaptation. In Greece, solar power is the second major renewable energy, constituting an increasingly important component of the future low-carbon energy portfolio. In this work, we propose the use of a high-resolution regional climate model (Weather Research and Forecasting model, WRF) to generate a solar climate atlas for the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…For example, in different locations in Cyprus, monthly averages of daily percentage of sun-shine of ~60% in winter and ~90% in summer have been reported [14,15]. The studies of Kalogirou et al, [16] and Pashiaridis et al, [17] report cumulative annual global horizontal irradiance (GHI) of 6700 -7300 MJ/m 2 for different sites in Cyprus, which is generally above the average annual GHI in the territory of southern European countries such as Greece and Italy [18,19] and comparable with average annual GHI reported for different sites in Malta and Andalusia, Spain [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…For example, in different locations in Cyprus, monthly averages of daily percentage of sun-shine of ~60% in winter and ~90% in summer have been reported [14,15]. The studies of Kalogirou et al, [16] and Pashiaridis et al, [17] report cumulative annual global horizontal irradiance (GHI) of 6700 -7300 MJ/m 2 for different sites in Cyprus, which is generally above the average annual GHI in the territory of southern European countries such as Greece and Italy [18,19] and comparable with average annual GHI reported for different sites in Malta and Andalusia, Spain [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…The model evaluation showed by comparison to the available observational products that the downscaling reanalysis datasets to the domain of Greece produced reliable results at various temporal scales for minimum and maximum temperatures (TX and TN) and precipitation (PR), highlighting the added value of the downscaling methodology. This model was also validated for mean seasonal daily Global Horizontal Irradiation (GHI), clear-sky fraction/days (Katopodis et al 2020) and wind speed at 10m (Katopodis et al 2021). It is worth also mentioning that other relevant studies have indicated improved description of simulation results using the WRF model, clearly supporting its use as a regional climate model (Soares et al 2012b The selected GCM for our study was the EC-Earth model of the ECMWF Integrated Forecast System (IFS) that has been incorporated in CMIP5 and more recently in CMIP6 (Vautard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical Weather Prediction (NWP) [7]. Typical NWP models include European Centre for Medium-Range Weather Forecasts (ECMWF) [8], Fifth-generation Mesoscale Model (MM5) [9] and Weather Research and Forecasting (WRF) [10]. Mathiesen and Kleissl [11] evaluated the numerical forecast of daytime solar radiation intensity in the United States.…”
Section: Introductionmentioning
confidence: 99%